PENGARUH PEMBIAYAAN DAN ENTREPRENEURSHIP KEPALA SEKOLAH TERHADAP EFEKTIFITAS SEKOLAH DI SEKOLAH MENENGAH PERTAMA (SMP) KOTA PEKANBARU - Gunawan Nur; Azhar Azhar; Nurpit Junus (Universitas Riau, 2017)
The purpose of this research aim to influence cost (x1) and headmasterentrepreneurship ( x2 ) toward school effectivity (Y) at junior high school (SMP) atPekanbaru.Population in this researchi is principal of junior high school (SMP) at Pekanbaruand respondent is 112, research sampel amount to 88 respondent. The instrument validity wastested by using product moment, correlation formula,while realibility coefficient intrumentcalculated by alpha coefficient.Requirement of data analisis was normality test using SPSS.Data analis used simple and partial correlation then simple and multiple regressions.Thisreseachshowed that: First, the was positive effect betwen cost (x1) of the school effectivity(Y) with correlation coefficient rY1= 0,343 and regressions equation ˆ = 64,449 + 0,481X1.Second, there was positive effect betwen headmaster entrepreneurship ( x2 ) of the schooleffectivity (Y) correlation coefficient rY2= 0,425 and regressions equation= 59,210 + 0,493X2.Third, , there was positive effect betwen cost (x1) and headmaster entrepreneurship towardschool effectivity (Y) togetherness with correlation coefficient rY1 = 0,538 and regressionsequation= 42,023 + 0,308X1 + 0,371X2. Conclusion of this research showed cost and headmasterentreprenership could be influence to school effectivity at junior high school at Pekanbaru